Preparation of low-cost activated carbons from amazonian nutshells for CO2 storage. (January 2021) - Serafin, Jarosław; Ouzzine, Mohammed; Cruz Junior, Orlando F.; Sreńscek-Nazzal, Joanna
Abstract: Low-cost carbonaceous adsorbents with microporous structures and a moderate specific surface area (up to 1630 m 2 g −1 ) were prepared from different amazonian nutshells by one-step chemical activation with KOH for CO2 storage. In-depth micropore structure analysis and surface characterization were performed using adsorption isotherms at 298 K and carbon dioxide isotherms at 273 K. The Brazilian nutshell and Cascara Capuassau exhibit a remarkable CO2 uptake capacity of 5.14 mmol g −1 and 5.13 mmol g −1 at 273 K, respectively up to 1 atm. The highest CO2 adsorption at 298 K equal to 3.67 mmol g −1 was observed on activated carbon produced from Cascara Capuassau. The low-pressure CO2 capacities are well correlated with the volume of small micropores (<0.7 nm) rather than the total micropore volume and surface area. The great mesoporosity of activated carbons is beneficial to ensure higher CO2 capture at high uptake pressure. Highlights: Demonstration of one-step chemical synthesis procedure for activated carbon from biomass. Characterization studies and several analytical techniques were carried out to determine CO2 sorbent capacity. Activated carbons from amazonian nutshells represents an interesting alternative to CO2 capture. The amount of CO2 adsorbed mostly depends on the population of narrow micropores (<1 nm).